Obesity affects the proteome profile of periodontal ligament submitted to mechanical forces induced by orthodontic tooth movement in rats - Marcantonio, Camila Chierici [UNESP]; Lopes, Maria Eduarda Scordamaia [UNESP]; Mofatto, Luciana Souto; Salmon, Cristiane Ribeiro; Deschner, James; Nociti-Junior, Francisco Humberto; Cirelli, Joni Augusto [UNESP]; Nogueira, Andressa Vilas Boas [UNESP] (Elsevier, 2022)
The prevalence of obesity has increased significantly worldwide. Therefore, this study aimed to evaluate the influence of obesity on the proteomic profile of periodontal ligament (PDL) tissues of rat first maxillary molars (1 M) submitted to orthodontic tooth movement (OTM). Ten Holtzman rats were distributed into two groups (n = 5): the M group (OTM), and the OM group (obesity induction plus OTM). Obesity was induced by a high-fat diet for the entire experimental periods After that period, the animals were euthanized and the hemimaxillae removed and processed for laser capture microdissection of the PDL tissues of the 1 M. Peptide extracts were obtained and analyzed by LC-MS/MS. Data are available via ProteomeXchange with identifier PXD033647. Out of the 109 proteins with differential abundance, 49 were identified in the OM group, including Vinculin, Cathepsin D, and Osteopontin, which were selected for in situ localization by immunohistochemistry analysis (IHC). Overall, Gene Ontology (GO) analysis indicated that enriched proteins were related to the GO component cellular category. IHC validated the trends for selected proteins. Our study highlights the differences in the PDL proteome profiling of healthy and obese subjects undergoing OTM. These findings may provide valuable information needed to better understand the mechanisms involved in tissue remodeling in obese patients submitted to orthodontic treatment. Significance: The prevalence of obesity is increasing worldwide. Emerging findings in the field of dentistry suggest that obesity influences the tissues around the teeth, especially those in the periodontal ligament. Therefore, evaluation of the effect of obesity on periodontal tissues remodeling during orthodontic tooth movement is a relevant research topic. To our knowledge, this is the first study to evaluate proteomic changes in periodontal ligament tissue in response to the association between orthodontic tooth movement and obesity. Our study identified a novel protein profile associated with obesity by using laser microdissection and proteomic analysis, providing new information to increase understanding of the mechanisms involved in obese patients undergoing orthodontic treatment which can lead to a more personalized orthodontic treatment approach.
Keywords: Cathepsin D; Obesity; Orthodontic tooth movement; Osteopontin; Proteomics; Vinculin